Le juge constitutionnel face au conflit politique : le cas du processus souverainiste catalan - Gennaro Ferraiuolo (Cahiers de Civilisation Espagnole Contemporaine)
The article analyzes the role played by the Spanish Constitutional Court (tc) in relation to the Catalan matter. The first part adopts a theoretical approach to study the position of the constitutional judge in systems that are nationally complex. The work then analyzes the relevant case law of the tc, from the well-known judgment 31/2010 on the Catalan Statute to the most recent decisions regarding the explosion of the national conflict.